Optimization Strategy for the Local Culture-Based Creative Economy as a Driver of the Real Sector in Polowijen Cultural Village - Diana Saputri Sri Wahyuningtyas; Farida Rahmawati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The transformation towards a knowledge- and creativity-based economy opens opportunities for local culture to become a driver of the real sector. However, at the community level, cultural potential is often not strategically managed due to institutional and managerial weaknesses. This study aims to analyze strategies for optimizing the local culture-based creative economy in the Polowijen Cultural Village (KBP) in Malang City. The method used is a mixed method approach through qualitative identification of strategic factors and quantitative analysis using the IFAS, EFAS, IE, SWOT, and QSPM matrices. The results show that KBP has a strong internal position (3.15) and supportive external conditions (2.89), thus placing it in the growth and build quadrant. The priority strategy established is the development of cultural educational tourism integrated with crafts, performing arts, and local MSMEs. These findings confirm that local culture can function as a driver of the real sector through the creation of added value, employment opportunities, and economic multiplier effects. Institutional strengthening and digitalization of promotion are key to sustainable development.